Engineered bone cement trigger bone defect regeneration - Xia, Yuanliang; Wang, Hengyi; Li, Yuehong; Fu, Changfeng (Frontiers in Materials, 2022)
Bone defects, which can be caused by factors such as trauma, tumor, or osteomyelitis, are clinically common. They lessen the weight a bone is able to bear and cause severe pain to the patient. Although bone transplantation is the gold standard for treating bone defects, it is not suitable for all patients due to its poor availability, risk of spreading disease, and possibility of requiring a secondary surgery. Bone cement as a filler for bone defects can fill any shape of bone defect, and can quickly solidify when injected, providing mechanical strength sufficient for supporting the normal physiological activities of the bone. However, traditional bone cement lacks the ability to induce bone regeneration. Recently, various methods for enhancing the bone regeneration ability of bone cement have been developed, such as adding bone morphogenetic proteins, mesenchymal stem cells, and inorganic substances to bone cement. These methods not only ensure the original biological properties of the bone cement, but also improve the bone cement in terms of its mechanical strength and ability to induce bone regeneration. The aim of this review is to overview the process of bone regeneration, introduce improved bone cement formulations designed to promote bone regeneration, and discuss the clinical application of bone cement and its possibilities for future improvement.